Antiretroviral Resistance and Pregnancy Characteristics of Women with Perinatal and Nonperinatal HIV Infection. (19th June 2016) - Lazenby, Gweneth B.; Mmeje, Okeoma; Fisher, Barbra M.; Weinberg, Adriana; Aaron, Erika K.; Keating, Maria; Luque, Amneris E.; Willers, Denise; Cohan, Deborah; Money, Deborah
Abstract : Objective . To compare HIV drug resistance in pregnant women with perinatal HIV (PHIV) and those with nonperinatal HIV (NPHIV) infection. Methods . We conducted a multisite cohort study of PHIV and NPHIV women from 2000 to 2014. Sample size was calculated to identify a fourfold increase in antiretroviral (ARV) drug resistance in PHIV women. Continuous variables were compared using Student'st -test and Wilcoxon rank-sum tests. Categorical variables were compared usingχ 2 and Fisher's exact tests. Univariate analysis was used to determine factors associated with antiretroviral drug resistance. Results . Forty-one PHIV and 41 NPHIV participants were included. Women with PHIV were more likely to have drug resistance than those with NPHIV ((55% versus 17%, p = 0.03 ), OR 6.0 (95% CI 1.0–34.8), p = 0.05 ), including multiclass resistance (15% versus 0, p = 0.03 ), and they were more likely to receive nonstandard ARVs during pregnancy (27% versus 5%, p = 0.01 ). PHIV and NPHIV women had similar rates of preterm birth (11% versus 28%, p = 0.08 ) and cesarean delivery (47% versus 46%, p = 0.9 ). Two infants born to a single NPHIV woman acquired HIV infection. Conclusions . PHIV women have a high frequency of HIV drug resistance mutations, leading to nonstandard ARVs use during pregnancy. Despite nonstandard ARV use during pregnancy, PHIV women did not experience increased rates of adverse pregnancy outcomes.